Placental disorders in displaced pregnant women who are in persistent stress - I.A. Zhabchenko; T.D. Zadorozhna; S.V. Tertychna-Teliuk; V.K. Likhachov; N.H. Korniiets; V.F. Oleshko; Y.M. Slіepichko (Publishing House TRILIST, 2023)
Objectives: to determine morphological and immunohistochemical changes in the placentas of displaced pregnant women in order to further improve the antenatal monitoring program. Materials and methods. 96 displaced pregnant women (the main group) took part in the prospective study, who depending on the therapy were divided into: group I - 65 pregnant women who were monitored according to generally accepted recommendations and received routine therapy for prolonging pregnancy, group II - 31 pregnant women who received the proposed treatment and prophylactic complex (micronized progesterone, magnesium citrate in combination with pyridoxine hydrochloride, iron fumarate, a multivitamin complex with 200 mg of docosahexaenoic acid, complex of medical and psychological support for pregnant women). The control group consisted of 39 pregnant women living at territories controlled by Ukraine. The duration of observation was 2 years. Placentas were examined by organometric, macroscopic, general histological and immunohistochemical methods. Results. Organometrically, placentas in the group I had a significant decrease in thickness, mass and size. Edema of Wharton jelly was significantly more pronounced in this group, and in the lumen of vessels there was a more pronounced parietal formation of fibrin blood clots. Manifestations of ischemic infarcts and blood clots, which were located mainly in the paracentral and peripheral zones, were found significantly more frequently among women of the group I. Histologically, tissue changes were noted in the placentas in the group I, which are manifestations of placental damage and characterized by a partial decrease in maternal-fetal-placental perfusion. These changes were combined with focal edema in decidual tissue and dystrophy in decidual cells. In the placentas of women of the group I an uneven focal, sometimes pronounced proliferation of syncytial nodules of a more widespread nature was noted, which is a marker of cellular aging associated with adverse factors affecting the mother's body. Also, foci of maternal infarcts were noted in the group I, which is associated with a decrease in maternal perfusion in the vessels of the placental barrier. Immunohistochemically, vacuolization and uneven chromatin arrangement were observed in the nuclei of villi cells during Ki-67 immersion, which indicated a decrease in regenerative responses in the placental barrier in groups I and II, especially with elevated cortisol levels. Immunohistochemical studies of the pro-apoptotic marker P-53 showed expression in single nuclei of villi stroma cells. Conclusions. The detected changes in the structures of the placental barrier indicate the predominance of placental disorders in the group I compared to the group II and control groups, especially in the syncytium of the villi, which led to a violation of the placenta functioning. Morphological studies confirmed the significant impact of long-term chronic stress on the formation and functioning of the uterine-placental-fetal complex, as well as the effectiveness of the proposed treatment in preventing the identified disorders.